"الرقابة على ميزانية البلدية - بالتركيز على الرقابة المالية - دراسة حالة ميزانية بلدية قمار - ولاية الوادي -" - نويوة, يمينة; حوقة, عتيقة; بن عون, مفيدة (University of eloued جامعة الوادي, 2018)
الملخص: تعالج الدراسة واقع الرقابة القبلية والبعدية على ميزانية البلدية وكيف يمكن تفعيلها للحفاظ على المال العام، وبالأخص الرقابة على النفقة العمومية من قبل أجهزة الرقابة القبلية أو ما اصطلح عليها بالرقابة الوقائية، وهذا للدور المهم الذي تقوم به في معالجة النفقة العمومية قبل صرفها. أما الرقابة البعدية فهي رقابة علاجية وتتم بعد تنفيذ الميزانية، وتقوم على أساس مدى تطبيق البلديات للقوانين والمراسيم في الالتزام بالنفقة وتحصيل الإيراد. و بهدف معالجة الإشكالية تطرقنا في الجانب النظري إلى آليات الرقابة القبلية والبعدية بمختلف أجهزتها وهيئاتها وفي الجانب التطبيقي أسقطنا نماذج عملية على مستوى ميزانية بلدية قمار تبرز آلية كل جهاز أو هيئة واقعيا على الميزانية، ولإثراء الموضوع تطرقنا إلى معوقات تحول دون تفعيل الرقابة القبلية والبعدية وبالأخص أجهزة الرقابة المالية ، وهذا بغية وصول أجهزة الرقابة المالية في الجزائر إلى تطبيق المعايير التي تدعو إليه المنظمات INTOSAI وARBOSAI وأهمها رقابة الأداء والاستقلالية من اجل فعالية العمل الرقابي وكذلك إعطاء مكانه خاصة للرقابة الداخلية خاصة على مستوى البلديات . This research deals with the reality of pre-audit and post-audit over the municipal budget and how it can be activated to preserve public funds, particularly, the supervision of public expenditure by the pre-audit bodies or what is called the preventive control (audit) and this role is important in the treatment of public expenditure before disbursement.Concerning the post-audit which is a curative (corrective) control that is carried out after the implementation of the budget. It is based on the extent of the implementation of the laws and the decrees by the municipalities and their commitment to maintenance and collection of revenue. In order to deal with the issue, in the theoretical aspect, we discussed the mechanisms of pre and post-audit in all its bodies. In the practical side, we dropped practical models at the budget of the municipality of Guémar, realistically highlighting the mechanism of each body or entity on the budget. To enrich the subject, we dealt with obstacles that prevent the activation of the pre-audit and the post-audit, especially the financial control bodies. This is in order for the financial control bodies in Algeria to reach the standards that the organizations ARBOSAI and INTOSAI call for. The most important of these is the control of the performance and the independence for the effectiveness of the supervisory(control) work and also to give special place to internal control, especially at the municipal level.
مذكرة ماستر محاسبة
Keywords: الرقابة، ميزانية البلدية ، الرقابة المالية